The Step of Incorporation of Bacillus coagulans GBI-30 6086 Into “requeijão cremoso” Processed Cheese Does Not Affect Metabolic Homeostasis of Rats - Soares, Mariana B.; Santos-Junior, Valfredo A.; Tavares Filho, E. R.; Lollo, Pablo C. B.; Morato, Priscila N.; Amaya-Farfan, Jaime; Pereira, Eliene P. R.; Balthazar, Celso F.; Cruz, Adriano G.; Martinez, Rafael C. R.; Sant’Ana, Anderson S. (Frontiers in Microbiology, 2019)
Dairy product consumption is a common habit in Brazil. These products present a good matrix for probiotic incorporation. Thus, in this study the feasibility of producing a probiotic "requeijão cremoso" incorporated with B. coagulans GBI-30 6086 in three different steps and its metabolic effect in an animal model for two weeks has been evaluated. Wistar adult health rats were randomized into one to five groups (n=8 for each group): Control (C); “requeijão cremoso” without probiotic (RC); probiotic inoculated in the milk before pasteurization at 65ºC/30min (RPP); “requeijão cremoso” inoculated before the fusion step and consequently exposed to 90ºC/5min (RPF); and “requeijão cremoso” inoculated after fusion step, i.e., once the product temperature reached 50ºC (RPAF). At the end of treatment, analysis of molecular markers of proteins of stress and antioxidant system, HSP 25, 60, 70 and 90, SOD and catalase were performed in the animals’ muscles by Western Blot technique. The HSP25, HSP90 and catalase levels of C, RPP, RPF, and RPAF were similar, indicating that the homeostasis remained unchanged. The incorporation of B. coagulans GBI-30 6086 in the "requeijão cremoso" was shown to be stable and the microorganism remained viable in all steps tested. The incorporation of the probiotic strain in the fusion stage facilitated the technological process, since it allowed a better homogenization of the product and did not affect the maintenance of the metabolic homeostasis of rats.